Information Communication Technology (ICT) Facilities and Information Resource Sharing Activities in Federal University Libraries in North Central, Nigeria - Eromosele, Peace Osemudiamen; Ahmed, Abdulganiy O.; Madu, Evarest C. (Ghana Library Journal, 2022)
The research investigated the impact of Information Communication Technology (ICT) Facilities on Information Resource Sharing Activities in Federal University Libraries In North Central, Nigeria. The study was guided by four objectives and one null hypothesis. A descriptive survey was used with the target population of 121 librarians in the seven federal university libraries in North central, Nigeria. The questionnaire was used in data collection. 121 copies of the questionnaire were administered 102 were filled, returned and found usable representing an 87.2% response rate. Percentage, Means and standard deviation were used in data analysis and Pearson Product moment correlation was used to test the null hypotheses. The study found that the factors restricting the usage of ICT for information resource sharing in federal university libraries in North central, Nigeria, were inadequate funding and lack of ICT infrastructure and connectivity. H01 showed that there was a relationship between ICT and information resource sharing in federal university libraries in North central, Nigeria. The study found that the factors restricting the usage of ICT for information resource sharing in federal university libraries in North central, Nigeria, were inadequate funding and ICT infrastructure and connectivity. The paper recommended amongst others that federal universities in North Central Nigeria should ensure that the funds allocated to the university library should be increased and also should endeavour to provide adequate ICT facilities that are lacking such as video conferencing and intranet to enhance information resource sharing activities.